Evidence base for Collaborating, Learning, and Adapting: summary of the literature review (2020 update) - Learning Lab (USAID, 2020)
The LEARN contract and the United States Agency for International Development/Bureau of Policy, Planning, and Learning (USAID/PPL) are managing an area of work known as the Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer the following key learning questions: ● Does an intentional, systematic, and resourced approach to collaborating, learning, and adapting (CLA) contribute to organizational effectiveness and/or development outcomes? ● If so, how? And under what conditions? ● How do we know? How do we measure any contribution that CLA makes to development results? As we began this work, we identified the need to conduct a literature review looking at these questions to understand what is known, what remains unknown, and how others have tried to answer these questions to date. We were primarily interested in answering these questions: ● What evidence is there, if any, that collaborating, learning, and/or adapting contributes to organizational effectiveness, development outcomes, or both? What are the strongest pieces of evidence? ● Does the literature identify any factors critical to CLA that are not currently included in the CLA framework? ● Who else is working on measuring the impact of collaborating, learning and adapting? ● What methods and measures did researchers use to study the effects of collaborating, learning, and adapting? ● Where are there gaps in the research relevant to collaborating, learning, and adapting? ● When taken together, what practical guidance does the evidence for collaborating, learning, and adapting offer to practitioners and policy makers to improve organizational effectiveness and development outcomes?

What difference does CLA make to development? Key findings from a recent literature review (2020 update) - Learning Lab (USAID, 2020)
USAID’s Bureau for Policy, Planning and Learning and its LEARN support contract are working to integrate systematic, intentional and resourced collaborating, learning and adapting (CLA) throughout program planning and implementation to achieve more effective development programs. As part of this effort, USAID is exploring several approaches to understand whether and how strategic collaboration, continuous learning and adaptive management make a difference to organizational effectiveness and development outcomes. To begin this work, we have undertaken a foundational literature review of academic and gray literature to answer our key learning questions: • Does an intentional, systematic and resourced approach to collaborating, learning and adapting contribute to organizational effectiveness? To development outcomes? • If so, how? And under what circumstances? • How do we measure the contribution? The 13 key findings, mapped to the CLA Framework below, are described in greater detail in the following pages.

LEARN End of Contract Report - Learning Lab (USAID, 2020)
In September of 2014, USAID’s Office of Learning, Evaluation & Research (LER) awarded the Learning and Knowledge Management (LEARN) contract to Dexis Consulting Group and subcontractor RTI International.1 This document—the End of Contract Report—captures five and half years of results and reflections for our stakeholders. Our intention is to share the good and the bad, and while this report would not be considered a “tell all,” we think we have a story worth sharing, particularly to USAID CORs and AORs, activity managers, and other implementers of institutional support contracts.2 LEARN’s primary purpose was to support organizational change at USAID. More specifically, the contract was focused on helping USAID staff integrate collaborating, learning, and adapting (CLA) approaches into the design, implementation, monitoring, and evaluation of programs (what is known at USAID as the Program Cycle). It was clear that most USAID staff, whether they realized it or not, were already integrating CLA into their work to some extent. The focus of our efforts, therefore, was to make those practices more systematic, intentional, resourced, and ultimately more widespread throughout the Agency, which would have a ripple effect on implementing partners and even other stakeholders, such as host country governments. This was based on the theory—later borne out by evidence—that by becoming a better learning organization, USAID could be a more effective development organization. And that theory brought the USAID CLA team within USAID’s Bureau for Policy, Planning & Learning (PPL) and LEARN contractors together, driven by a shared purpose of improving how USAID does business. LEARN was designed based on this belief and, as you might expect from a learning-oriented contract, began with more questions than answers. Primary among those questions was: could an institutional support contract do more than carry out requested services—could it actually accelerate positive organizational change at USAID? And if so, how and under what conditions?